ANALISIS PERAN BADAN USAHA MILIK DESA (BUM DESA) REJEKI BAROKAH SEBAGAI UPAYA PEMBERDAYAAN MASYARAKAT DAN PEMBANGUNAN EKONOMI DESA SUMBERGONDO KECAMATAN BUMIAJI KOTA BATU - Amordiaz, Elmico Duta; Maryunani (Islamic Economics and finance in Focus, 2024)
Village-Owned Enterprises (BUM Desa) are village autonomous institutions managed by the community and village government to empower the community and strengthen the village economy. BUM Desa Rejeki Barokah is an institution in the village social and economic sector as a provider of village community services in the form of waste management and educational tourism in Sumbergondo Village, Bumiaji District, Batu City. The aim of this research is to determine the role of BUM Desa in improving the economy and empowering its community. The method used in the research is descriptive qualitative. Data collection through interviews with key informants and research informants, as well as through documentation of the results of Village BUM management. This research shows that the existence of BUM Desa improves the Village economy in the form of getting jobs as well as increasing the income of the people who are workers in each business unit and who are suppliers of raw materials in the business unit as well as the people who are customers in the Waste Bank business unit. Apart from that, the existence of BUM Desa is aimed at empowering village communities in the form of village communities being involved from establishment, implementation to reporting. Apart from that, BUM Desa collaborates with businesses and MSMEs owned by the community.